Effect of a focusing electric field on the formation of arc generated carbon nanotubes - Karmakar, Soumen; Nagar, Harshada; Pasricha, R.; Seth, T.; Sathe, V. G.; Bhoraskar, S. V.; Das, A. K. (Nanotechnology, 2006)
The effect of a focusing electric field on the formation of carbon nanotubes in a direct current arc-plasma is investigated. The hard deposits on the surface of the cathode are the main products, rich in multi-walled carbon nanotubes. It is seen that the focusing electric field has a distinct influence on the yield, purity and morphology of the nanotubes. The yield of the carbon nanotubes under the `focused field condition' has been found to be higher than that derived from the normal electrode configuration. It has been observed that the deposition of carbonaceous soot on the reactor wall is considerably reduced on application of the focusing electric field. Transmission electron microscopy has been used to determine the morphology of the nanotubes. In addition, Raman spectroscopy has helped in distinguishing the graphene-like structures from the disordered carbon networks and helped in analysing the morphology of the tubes. Thermal analysis gave a qualitative estimation of the relative yield of carbon nanotubes within the cathode deposits and their thermal stabilities. The crystalline nature of the samples has been confirmed by x-ray diffraction analysis. The results clearly indicate that the focusing electric field confines the positively charged carbon precursors within the cathode-anode space causing high relative yield and purity and has a distinct effect on controlling the inner diameter of the as-synthesized carbon nanotubes.

Electrokinetic properties of PMAA functionalized NiFe2O4 nanoparticles synthesized by thermal plasma route - Bhosale, Shivaji V.; Mhaske, Pravin; Kanhe, N.; Navale, A. B.; Bhoraskar, S. V.; Mathe, V. L.; Bhatt, S. K. (Solid State Physics: Proceedings of the 58th Dae Solid State Physics Symposium 2013, PTS A & B, 2014)
The magnetic nickel ferrite (NiFe2O4) nanoparticles with an average size of 30nm were synthesised by Transferred arc DC Thermal Plasma route. The synthesized nickel ferrite nanoparticles were characterized by TEM and FTIR techniques. The synthesized nickel ferrite nanoparticles were further functionalized with PMAA (polymethacrylic acid) by self emulsion polymerization method and subsequently were characterized by FTIR and Zeta Analyzer. The variation of zeta potential with pH was systematically studied for both PMAA functionalized (PNFO) and uncoated nickel ferrite nanoparticles (NFO). The IEP (isoelectric points) for PNFO and NFO was determined from the graph of zeta potential vs pH. It was observed that the IEP for NFO was at 7.20 and for PNFO it was 2.52. The decrease in IEP of PNFO was attributed to the COOH functional group of PMAA.
Keywords: IEP; NiFe2O4; PMAA; Thermal plasma; Zeta potential